Effect of chemical and heat treatment on the nutritive value of low quality feedstuffs - Djafar, M. Ishak; Hussain, Khairuddin (Veterinary Association Malaysia, 1976)
In vivo and in vitro digestibility studies were conducted on untreated and on 3% NaOH treated sawdust and corncob feedstuffs. Results showed that sawdust or corncob can replace 28% of other roughages in a feed mixture. Chemical end combined chemical/heat treatment improved the diqestibilties of dry matter, crude protein, crude fibre, gross energy and also the feed intake (P < 0.01). There was only a slight difference between chemical treatment and the combined chemical/heat treatment. However, there was a highly significant difference between corncob and sawdust, the former was much superior than the latter. The cost of the sawdust or corncob feed mixture was much cheaper than a mixture of 80% grass pellets and 20% maize